Contemporary utility of music therapy as described in Vedic literature - Ghazala (Knowledgeable Research A Multidisciplinary Journal, 2025)
"Mantra means 'Mannaat Trayate Iti Mantra' which means that by properly pronouncing it with vowels like Udatta, Anudat and Svarit, our mind can quickly come in contact with 'Shabda Brahma'. It means that vowels or musical prayers not only make the mantras well-formed but the pronunciation of vowels makes various parts of our body creative." Today's scholars also believe in the power of mantras. The power of words generates electronic magnetic waves. Which increases their activity by having a desired effect on the nervous system. Various experiments related to the effect of repeating or chanting mantras and this study is also going on under Semiotics, which is enough to prove that musical pronunciation of mantras and its chanting has a positive effect on the body, mind and nature. The basis of Indian knowledge and science is the book 'Veda'. Vedas are called Apaurusheya because they contain all the arts and sciences. Mantras related to Vedas are found equally in Rigveda and Yajurveda -Tasmat yagyatsarvahutah richah samani jagyare.Chhandansi Jagyire Tasmadyajustasmadjayat.That is, from that supreme God, Rigveda, Yajurveda, Samaveda and Chhandansi i.e. Atharvaveda have originated.